Streaming motions of galaxy clusters within 12 000 km s(-1) - III. A standardized catalogue of Fundamental Plane data - Hudson, M; Lucey, JR; Smith, R; Schlegel, D; Davies, R (2001)
We report the construction of a new, standardized all-sky catalogue of Fundamental Plane (FP) data from early-type galaxies in clusters, for peculiar velocity applications. This catalogue is based on a compilation of spectroscopic and photometric data consisting of data reported in previous papers of this series, plus data from published sources. We compare velocity dispersion and Mg2 line-strength data from 27 sources, and determine the corrections that bring all data sets on to a standardized system. For the velocity dispersions, the corrections are typically at the level of ∼0.015 dex, corresponding to 5 per cent in the FP-estimated distance. The uncertainties in these corrections, however, are considerably smaller: the new data obtained by our group are closely matched on to the standard system, with systematic uncertainties at the level of ∼0.005 dex in velocity dispersion <2 per cent in distance). In this respect our catalogue significantly improves upon previously published FP data sets. For the Mg2 line-strength index, corrections are typically at the level of 0.01 mag, but the uncertainties in these corrections are only ∼0.002 mag. A similar procedure is employed to compare photometric data from nine different sources, correcting for the average colours of early-type galaxies. We focus on the combination of parameters appearing in the FP, XFP = log Re - 0.32〈μ〉e, where Re and 〈μ〉e are the effective radius and effective surface brightness, respectively. For the data sets considered here we show that no further corrections are required to XFP, given the typical systematic zero-point uncertainties per data source (0.003-0.006 dex, or 0.7-1.4 per cent in distance). Finally, we use redshift data to assign galaxies to clusters in an objective way. We present a master catalogue of FP data for 699 galaxies in 56 clusters, the largest high-quality data set of its kind. These data will be used in future papers to determine the distances and peculiar velocities of these clusters, and thus probe the peculiar velocity field within 12 000 km s-1.